The Judicial Reorganization under the Approach of the New Brazilian Civil Procedure Code - Vale, Maria Cláudia Viana Hissa Dias do (2016)
This article aims to demonstrate that the new civil procedure order allowed for a contemporary analysis of judicial reorganization procedures, through the adoption of new guidelines that ensure the fair distribution of the burdens arising from the overcoming of the crisis. Among the innovations, there are the alternative methods of conflict resolution, which are capable of reducing the backlog of judicial demands, substituting them by a more democratic management of processes that includes all involved parties. It is concluded that, although the adoption of these innovations are allowed under the Law 11.101/2005, they will be chosen on a case-by-case basis.